Primary ciliary dyskinesia ciliated airway cells show increased susceptibility to Haemophilus influenzae biofilm formation. Issue 3 (10th September 2017) - Walker, Woolf T.; Jackson, Claire L.; Allan, Raymond N.; Collins, Samuel A.; Kelso, Michael J.; Rineh, Ardeshir; Yepuri, Nageshwar R.; Nicholas, Ben; Lau, Laurie; Johnston, David; Lackie, Peter; Faust, Saul N.; et al.
Non-typeable Haemophilus influenzae (NTHi) is the most common pathogen in primary ciliary dyskinesia (PCD) patients. We hypothesised that abnormal ciliary motility and low airway nitric oxide (NO) levels on airway epithelial cells from PCD patients might be permissive for NTHi colonisation and biofilm development. We used a primary epithelial cell co-culture model to investigate NTHi infection. Primary airway epithelial cells from PCD and non-PCD patients were differentiated to ciliation using an air–liquid interface culture and then co-cultured with NTHi. NTHi adherence was greater on PCD epithelial cells compared to non-PCD cells (p<0.05) and the distribution of NTHi on PCD epithelium showed more aggregated NTHi in biofilms (p<0.001). Apart from defective ciliary motility, PCD cells did not significantly differ from non-PCD epithelial cells in the degree of ciliation and epithelial integrity or in cytokine, LL-37 and NO production. Treatment of PCD epithelia using exogenous NO and antibiotic significantly reduced NTHi viability in biofilms compared with antibiotic treatment alone. Impaired ciliary function was the primary defect in PCD airway epithelium underlying susceptibility to NTHi biofilm development compared with non-PCD epithelium. Although NO responses were similar, use of targeted NO with antibiotics enhanced killing of NTHi in biofilms, suggesting a novel therapeutic approach. Ex vivo study shows PCD airways risk NTHi biofilm colonisation; novel NO drug overcomes antibiotic tolerance http://ow.ly/GrXC30e4Tqv